Socio-ecological dynamics of Andean treelines in the 21st century - Peyre, Gwendolyn; Zuñiga, Enrique; Cornejo Paredes, Andrea; Paja Medina, Aremi; Sulla Torres, Jose Alfredo; Zúñiga Carnero, Manuel; Rosas Paredes, Karina (Frontiers in Ecology and Evolution, 2025)
Andean treelines are sensitive ecotones that are being increasingly threatened by both the climatic and anthropogenic facets of global change. Although they have received substantial scientific focus over the last decades, we still miss a comprehensive socio-ecological overview at the continental scale. This mini review aims to compile existing research on Andean treelines and offer a synthetic outlook on their geography, as well as their environmental and human drivers. We conducted an extensive search of scientific literature focused principally on ISI Web of Knowledge sources and spanning over the last two decades. It is established that Andean treelines vary in elevation according to their position in the cordillera, mostly due to mountain mass effects and latitudinal gradients, and the local topography. Temperature and moisture availability are significant drivers shaping Andean treelines, but seasonality and extreme events gain in importance with increasing latitude and climate change. Moreover, human influence has transformed treeline areas for millenia, by affecting their position, composition and ecological functions. Agriculture, livestock grazing and fires are primarily responsible for stalling many Andean treelines in their upslope migration today. This mini-review sheds light on the current state of Andean treelines today and suggests future pathways with anticipated opportunities for conservation and sustainable restoration. For instance, we stress the need for future research in species and community modelling to predict composition and distribution changes in forest and non-forest vegetation under global change scenarios.